2003
DOI: 10.1590/s0101-81752003000200007
|View full text |Cite
|
Sign up to set email alerts
|

External factors determining breeding season in the red mangrove crab Goniopsis cruentata (Latreille) (Crustacea, Brachyura, Grapsidae) on the São Paulo State northern coast, Brazil

Abstract: This study evaluated the influence of the water and air temperatures, pluviosity and photoperiod on the breeding season of Goniopsis cruentata (Latreille, 1803), in Ubatuba littoral, southeastern Brazilian coast. Monthly collections were conducted out from January/95 to December/96 in an estuarine area from 23º29'10"-23º29'45"S to 45º09'10"-45º10'00"W. Water and air temperature variation showed the highest correlation coefficient with the frequency of ovigerous females, r² = 0.73 and 0.68, respectively. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
2
16
1
9
Order By: Relevance
“…Este fator ambiental torna-se de grande importância, limitando a dispersão das zoeas em nível horizontal, além de promover uma redução deste período crítico, quando o animal é mais suscetível à predação (PINHEIRO et al, 1994). Além disso, a temperatura influencia a duração do período reprodutivo de algumas espécies de Brachyura exploradas comercialmente, como G. cruentata e U. cordatus (BOTELHO et al, 1999;COBO & FRANSOZO, 2003).…”
Section: Discussionunclassified
“…Este fator ambiental torna-se de grande importância, limitando a dispersão das zoeas em nível horizontal, além de promover uma redução deste período crítico, quando o animal é mais suscetível à predação (PINHEIRO et al, 1994). Além disso, a temperatura influencia a duração do período reprodutivo de algumas espécies de Brachyura exploradas comercialmente, como G. cruentata e U. cordatus (BOTELHO et al, 1999;COBO & FRANSOZO, 2003).…”
Section: Discussionunclassified
“…The first hypothesis is more reasonable, given that slow embryonic development is normally associated to low salinity (LIMA et al 2006), a fact that differs from the conditions of Itaipu Lagoon. In relation to the molt cycle, COSTA & NEGREIROS-FRANSOZO (1998) Callinectes danae Smith, 1869, COBO & FRANSOZO (2003 Goniopsis cruentata Latreille, 1803 and CASTIGLIONI & NEGREIROS-FRANSOZO (2006b) U. rapax, found that the highest molt activity occur in juvenile crabs and that the molt activity decreases after the puberty molt. This is probably related to the investment in the reproductive process, since the beginning of the reproductive activities lead to a decrease in the growth rate, especially the females that stop the growth when bearing eggs and, consequently, stop the molt activities (CRANE 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Monthly fecundity was estimated by counting eggs by the volumetric method, using a total volume of 30 ml and subsamples of 1 ml (DÍAZ et al 1983, COBO & FRANSOZO 2003. Oneway ANOVA was employed, before testing the normality and variance homogeneity assumptions, to compare fecundity across seasons.…”
mentioning
confidence: 99%
“…En algunas especies de cangrejos la actividad reproductiva es continua durante todo el año (FEDOSEYEB, 1988); tal es el caso de Goniopsis cruentata (Latreille, 1803) en Brasil (COBO & FRANSOZO, 2003). En otras, como Ucides cordatus (Linnaeus, 1763) la reproducción se desarrolla en períodos anuales que pueden variar en duración (DALABONA & LOYOLA & SILVA, 2005).…”
unclassified